“Você tem fome de quê?”: movimentos (e)m currículos de uma escola do ensino médio em Ipiaú, Bahia - Brandão, Elenilda Alves (2017)
This dissertation presents a qualitative research in education, inserted in thought movements conforming to philosophy of the difference, based on Deleuze’s event concepts and based on the power of life according to Espinosa. The choices we make here it is for a curriculum that goes beyond ideas that are ripe to be used by subjects. It searches on MarlucyParayso and Sandra Corazza's readings the hungers, the desire to satisfy them, establishing other possibilities for thinking, studying and practicing curricula. Data-building process happened at the public school Luiz Eduardo Magalhães between 2015 and 2016 years in Ipiaú town and involved nine students of three grades from high school, three women teachers and one skater who is a former student of this school. The cartography, which permeated the way of thinking this writing-research was based on case study, articulating the bricolage as methodology in movement. First of all, I used some (un)organized strategies, such as: dynamic workshops with music and drawing/painting on canvas, photography production, besides parody, T-shirt making, conversation groups on whatsapp and informal interviews. In this way, from material analyses produced by students and collaborators in our bricoleur experiences, we undertake (im) possibilities to understand High School curricula, as means that (re) configure happenings that push and unleash the intense flow of life like creative potency.